Our spatial reality and God - Jan Muis (AOSIS, 2021)
Modern scientific models of cosmological space and the theological concept of God’s immensity seem to exclude the possibility that God himself is personally present with us humans at particular places in space. Are God and our spatial reality incompatible? Or, is it possible to conceive the connection between God and space as ‘positive’, that is, in such a way that God himself can be fully and personally present with us at particular places in space? This essay explores how this question may be addressed in a theology which accepts the results of the natural sciences and acknowledges that God is the free creator of physical space. It describes how space can be conceptualised, and presents an overview of five different views on a positive relation between God and space in recent protestant theology. It concludes by some considerations on the question whether a positive relation between God and space requires that God himself is spatial.